2014
DOI: 10.5433/1679-0359.2014v35n1p251
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade fisiológica de sementes de pimenta obtidas em frutos de diferentes estágios e armazenadas

Abstract: ResumoO objetivo nesse trabalho foi avaliar a qualidade fisiológica de sementes de pimenta em frutos de diferentes maturações, submetidas ao repouso pós-colheita nos frutos e o armazenamento das sementes. As sementes utilizadas foram colhidas em julho de 2009, de plantas cultivadas em casa de vegetação da área de transferência de tecnologia da Embrapa Roraima. O delineamento experimental utilizado foi inteiramente casualizado em esquema fatorial 3x2x2 com 4 repetições. Na colheita foram retirados frutos imatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
(11 reference statements)
0
11
0
4
Order By: Relevance
“…The results suggest that C. pubescens seed development occurs at the same time of physiological fruit development and when occurs maturing (intense red color- Figure 1), seed quality starts to deteriorate (Bewley, Bradford, Hilhorst & Nonogaky, 2013;Espindola & Smiderle, 2014). However, the results are diferent for C. annuum, C. frutencens and C. baccatum (Ayala-Villegas et al, 2014;Bezerra et al, 2014;Spindola and Smiderle, 2014).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The results suggest that C. pubescens seed development occurs at the same time of physiological fruit development and when occurs maturing (intense red color- Figure 1), seed quality starts to deteriorate (Bewley, Bradford, Hilhorst & Nonogaky, 2013;Espindola & Smiderle, 2014). However, the results are diferent for C. annuum, C. frutencens and C. baccatum (Ayala-Villegas et al, 2014;Bezerra et al, 2014;Spindola and Smiderle, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…For total emergence (TE), the number of emerged seedlings was counted every third day (Pacheco & Zuñiga, 2007;Espindola & Smiderle, 2014). Mean emergence rate (MER), was defined as the number of seedlings that emerged in the interval i, divided by the number of days in the interval i.…”
Section: Evaluated Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it can increase the seed's production, because the ideal harvest span diminishes the quantity of immature seeds. Studies on maturation and seed harvest have been shown in a variety of crops (Freitas et al, 2007;Medeiros et al, 2010;Nakada et al, 2011;Duarte et al, 2012;Figueiredo Neto et al, 2012;Lima & Smiderle, 2014). However, in species where maturation is irregular, such as coriander, research are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Abud et al (2013) observed increases in the germination percentage of malagueta hot pepper seeds from 40 to 71 DAA and of biquinho hot pepper seeds between 40 and 79 DAA, which resulted in 86% and 89% germination, respectively. Similarly, Lima and Smiderle (2014) noted that malagueta hot pepper seeds extracted from "red" fruits (between 66 and 70 DAA) resulted in 84% germination. This variation in the number of days until the increase in germination that has been reported in the literature showed that growing environments had strong effects on intraspecific and species-related seed maturity in the Capsicum genus, which provided an explanation for the findings of these studies on hot peppers.…”
mentioning
confidence: 99%